Colonial Memory : Contemporary Women's Travel Writing in Britain and the Netherlands - Mul, Sarah de (2011)
Exploring the intersections between memory, gender and the postcolonial, Colonial Memory starts with the observation of a widespread cultural recall of colonial scenes and topics, a compulsion to return to the colonies that follows the belatedness of the postcolonial moment. Focusing on Britain and the Netherlands, the author explores the phenomenon of colonial memory through the specific genre of women's travel writing. De Mul criticizes postcolonial studies for its tendency to engage with general and abstract allegories of self and other, which she seeks to substitute with historicized accounts of the cultural frames that shape the contacts between Britain and the Netherlands and their respective (former) colonies, both in the past and the present.